Study Of the Effect of a Mixture of Extracts of Medicinal Plants on the State of the Gastric Mucosa in Gastropathy Induced by Indomethacin - Z.Z.Khakimov; G.Yu. Djanaev; Askarov O.O (Genius Journals, 2023)
In experimental animals, on the model of indomethacin-induced gastropathy, the influence of Lesbohol on the number of erosive-destructive lesions of the gastric mucosa was studied. It has been established that Lesbohol significantly reduces the number of point, strip-like and round lesions of the gastric mucosa. At the same time, Lesbohol surpasses the well-known gastroprotector misoprostol in its activity. It is believed that the mechanism of the gastroprotective activity of Lesbohol is due to the strengthening of the protective barrier of the gastric mucosa, as a result of the suppression of the intensity of free radical processes.
Keywords: NSAIDs; indomethacin; gastropathy; gastric mucosa